Conceptualising strategic communication management (SCM) in the context of governance and stakeholder inclusiveness - Benita Steyn; Estelle de Beer (Communicare)
The research objective for the study was to conceptualise strategic communication management (SCM) in the context of governance. Based on the insights obtained through the conceptual analysis, the core of corporate communication practice in the reflective paradigm is broadened from social responsibility to societal responsibility. Corporate communication, in its strategic role (SCM), therefore assists in solving or avoiding conflict between organisational behaviour and the public perception of how societally responsible organisations should operate. Furthermore, theoretical and conceptual linkages that emerged through the conceptual analysis suggest that the three meta-theoretical approaches initially selected for the governance domain (the triple bottom line, stakeholder, and stakeholder inclusiveness approaches) should also be added to the framework for SCM. It was also found that corporate communication (especially in its strategic role, known as SCM) can be regarded as a stakeholder orientated/responsible approach.